Jaroslav Horejc - nejen sochař : ze sbírky Tomáše Hejtmánka - Hejtmánek, Tomáš, 1967-; Steinhard, Erich, 1886-1941; Svojanovská, Barbara; Palán, Oto; Vano, Robert, 1948-; Šlapal, Filip, 1972- (Arthouse Hejtmánek, 2015)
Katalog výstavy, která seznámila veřejnost s díly sochaře Jaroslava Horejce ze sbírky Tomáše Hejtmánka.